Monitoring the Overall Quality of Groundwater Using a Geographic Information System in the Angads Plain (Oujda, Morocco) - Latifa Taoufiq; Ilias Kacimi; Mohamed Saadi; Nordine Nouayti; Nadia Kassou; Karima El-Mouhdi (The Scientific World Journal)
The future of groundwater is one of the key challenges for sustainable water management, hence the need to monitor its overall quality. The objective of this work is to assess the overall quality and determine the spatiotemporal evolution of the Angads aquifer in northeastern Morocco in 2014 and 2020, based on the parameters NH4+, NO3−, EC, Cl−, and FC, as well as the Geographic Information System (GIS). The results of the comparison of these five parameters between 2014 and 2020 show a general increase in NH4+ and a decrease in NO3− and FC at most sampling points. These changes could be attributed to a shift in pollution sources or biological processes affecting water quality. On the other hand, the stability of EC and Cl− levels suggests a consistency in the inputs of salts or minerals. The quality percentages show a decrease in good, poor, and very poor quality, following an increase in average quality, from 10.52% (in 2014) to 5.26% (in 2020), 31.57% (in 2014) to 21.05% (in 2020), 31.57% (in 2014) to 26.31% (in 2020), and 26.31% (in 2014) to 47.36% (in 2020), respectively. Spatial and temporal mapping of the quality over these 2 years shows that the deterioration continues toward the east, southeast, and southwest. This is justified by very high measurements of the parameters NO3−, EC, and Cl− at sampling points 2, 3, 4, 5, 7, 8, and 15 for 2014 and 2020, reaching 156 mg/L, 10,570 µS/cm, and 3790 mg/L in 2014 and 134 mg/L, 10,355 µS/cm, and 3597 mg/L in 2020, respectively, due to effluents from pollution points such as the Oujda public landfill, the wastewater treatment plant, and the former Sidi Yahya landfill to the west. On the other hand, in the north, northeast, and northwest, there has been an improvement in quality due to the remoteness of these pollution points. In order to protect this vital resource, recommendations need to be put in place, in particular by treating leachates so as to ensure that the quality of the water is not discharged directly into the aquifer or used for other purposes, and to avoid discharging effluent from the wastewater treatment plant into the natural environment.